Pembentukan Agen Perubahan “Aku Anak Berani” untuk Edukasi Bahaya Pornografi dan Pencegahan Kekerasan Seksual - Nadya Novia Rahman; Nanik Handayani; Ridha Wahyuni; Dian Dwi Nur Rahmah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The Internet is accessible to all age groups, including children. The ease of information obtained through the Internet causes vulnerable children to be exposed to pornographic content. Exposure to pornographic content in children can cause negative impacts both cognitively and behaviorally, one of which is behavior that leads to acts of sexual violence. The establishment of the Change Agent